2015
DOI: 10.1186/s13256-015-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Coil embolization of an anomalous bronchial artery originating from the left subclavian artery following arterial switch operation: a case report

Abstract: IntroductionBronchial arteries originate from the descending aorta at the level of the T5-T6 vertebrae following an intrapulmonary course along the major bronchi. When bronchial arteries take off from a vessel other than the descending aorta, the anatomy is defined as an anomalous origin of the bronchial artery.Case presentationA 3-day-old boy from Kosovo with dextro-transposition of the great arteries who developed progressive heart failure required an emergency arterial switch operation. Because of persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Title and abstract screening resulted in the retrieval of 21 articles for full-text review and, finally, nine studies were deemed eligible for our analysis, as summarized in PRISMA chart (Figure S1). All studies were case reports 8-14 of patients requiring CC for hemodynamically significant MAPCAs following ASO for d-TGA, while only one study 1 was a retrospective single-center study reporting on 15 patients. The study origin was Europe in 67% (6/9) of the cases and Asia in the rest (33%, 3/9) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Title and abstract screening resulted in the retrieval of 21 articles for full-text review and, finally, nine studies were deemed eligible for our analysis, as summarized in PRISMA chart (Figure S1). All studies were case reports 8-14 of patients requiring CC for hemodynamically significant MAPCAs following ASO for d-TGA, while only one study 1 was a retrospective single-center study reporting on 15 patients. The study origin was Europe in 67% (6/9) of the cases and Asia in the rest (33%, 3/9) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, unrepaired MAPCAs that are significant can contribute arterial blood flow to the pulmonary system at systemic pressures. 13,14 Wipf et al 1 found that clinically significant MAPCAs are present more often in d-TGA with decreased O 2 saturations, thus providing some credence to the hypothesis that hypoxemia may trigger these lesions. In addition, they highlight the role of chest wall stress and pleural inflammation associated with mechanical ventilation while in the ICU as a trigger for the formation of collaterals.…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation